Capacity Enhancement and Agribusiness Development: A Case Study of Rubber and Palm Oil Farmers in Kelian Village - Toyibulah, Yoga; Nugroho, Agung Enggal; Indana, Khoiru; Safitri, Apdila; Aprylasari, Dede (Jurnal Pengabdian West Science, 2025)
Abstract: This community service activity was carried out in Kelian Village, an area with significant potential in the agricultural and smallholder plantation sectors but facing various structural challenges such as limited infrastructure, market access, and farmer institutional capacity. This activity aimed to increase community capacity through a participatory approach that included identifying local potential, training in cultivating superior commodities (rubber and smallholder oil palm), strengthening farmer group institutions, and developing community action plans. The methods used included direct observation, focus group discussions, participatory mapping, and technical and institutional training. The activity results showed an increase in community understanding of sustainable cultivation practices, the formation of new farmer groups, and a growing collective awareness to transform towards a more independent and competitive agricultural system. Further mentoring, locally based training, and multi-stakeholder collaboration are recommended to support the sustainability of the initiatives that have been initiated. This experience demonstrates that a participatory approach effectively builds social capital and strengthens the foundations of inclusive and sustainable village development.